Perancangan Sistem Kontrol dan Monitoring Suhu Jarak Jauh Memanfaatkan Embeded System Berbasis Mikroprosesor W5100 dan AT8535 - Fauzan Nurahmadi (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2013)
Today’s Internet network getting faster and have been entered basic human need such as communication, monitoring, and controlling. The purpose of this system is to identify and manipulate the room temperature remotely.Remote temperature control system utilizing microcontroller-bases embedded system w5100 is a circuit system consisting of many system such as system monitoring and temperature control, where its results will be displayed periodically in a JAVA-bases application.Based on the result of trial that have been done, which compare the temperature on the application with the existing temperature of the object showed no significant difference similiarity, the w5100 microcontroller can be used and run well.Keywords—Temperature; Microcontroller; AT8535; W5100